Effect of ertugliflozin on left ventricular function in type 2 diabetes and pre-heart failure: the Ertu-GLS randomized clinical trial - Soo Lim; Jae Hyun Bae; Heran Oh; In-Chang Hwang; Yeonyee E. Yoon; Goo-Yeong Cho (Cardiovascular Diabetology, 2024)
Abstract Background The therapeutic effects of ertugliflozin, a sodium-glucose cotransporter 2 inhibitor, on cardiovascular outcome are not fully understood. This study aimed to evaluate the efficacy and safety of ertugliflozin on cardiac function in people with type 2 diabetes and pre-heart failure. Methods We conducted a 24-week randomized, double-blind, placebo-controlled trial involving individuals with type 2 diabetes inadequately controlled with antidiabetic medications. Participants with left ventricular hypertrophy, E/e’ >15, or impaired left ventricular global longitudinal strain (LVGLS) were randomized 1:1 to receive either ertugliflozin (5 mg once daily) or a placebo. The primary outcome was the change in LVGLS. Secondary outcomes included changes in left ventricular mass index (LVMI) and left ventricular ejection fraction (LVEF). Prespecified exploratory outcomes, including angiotensin-converting enzyme 2 (ACE2) and angiotensin (1–7) levels, were also assessed. Results A total of 102 individuals (mean age, 63.9 ± 9.2 years; 38% women) were included. The ertugliflozin group showed a significant improvement in LVGLS (− 15.5 ± 3.1% to − 16.6 ± 2.8%, P = 0.004) compared to the placebo group (− 16.7 ± 2.7% to − 16.4 ± 2.6%, P = 0.509), with a significant between-group difference (P = 0.013). Improvements in LVMI and LVEF were also observed. Additionally, significant reductions in HbA1c, systolic blood pressure, whole-body and visceral fat, uric acid, proteinuria, N-terminal pro–B-type natriuretic peptide, and lipoprotein(a) were noted. ACE2 and angiotensin (1–7) levels significantly increased in the ertugliflozin group compared to the placebo group and correlated with changes in LVGLS [r = 0.456, P < 0.001 for ACE2; r = 0.541, P < 0.001 for angiotensin (1–7)]. Adverse events were similar between the two groups. Conclusions This study demonstrated that ertugliflozin has beneficial effects on left ventricular function in individuals with type 2 diabetes and pre-heart failure, and it provided insights into potential underlying mechanisms. Clinical trial registration ClinicalTrials.gov Identifier: NCT03717194.